ANALISIS PENGELOLAAN KEUANGAN DAN KEKAYAAN DESA (Studi Kasus Desa Randubango Kecamatan Mojosari Kabupaten Mojokerto) - Ilham Riza Baihaqi; Abdul Wahid Mahsuni; Hariri Hariri (Universitas Islam Malang, 2022)
This study aims to determine the management of village finances and village wealth which includes planning accountability for village financial management in Randubango village and efforts to adjust to accountability and transparency. This study used a descriptive qualitative method. The information used in this study consisted of the village secretary, village treasurer, head of the BPD, community leaders. Data collection techniques used were interviews, observation, and documentation. The data analysis technique begins with checking the completeness of the data, checking the quality of the data, making data clustering and analyzing the data. The results of this study indicate that based on Permendagri Number 113 of 2014 concerning village financial management in general, Randubango village is in accordance with the stages stipulated in Permendagri Number 113 of 2014. Meanwhile, village wealth management is in accordance with existing provisions, namely governance, village development. and development and empowerment of rural communities. The Randubango village government does not experience obstacles in implementing village financial and wealth management.Keywords: Village Financial Management, Accountability, Transparency, Village Wealth